2007
DOI: 10.1007/s10751-008-9594-z
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Fe-bearing compounds in an Ultisol as determined with selective chemical dissolution and Mössbauer spectroscopy

Abstract: The distribution of Fe-bearing compounds in the silt and clay fractions from samples of a Chilean Ultisol developing on pyroclastic material was determined in this study. The mineralogical analysis was carried out mainly by Mössbauer spectroscopy at 298, 80 and 6 K, for samples before and after treatment with ammonium oxalate (OX). The 298 and 80 KMössbauer spectra reveal relatively complex mineral assemblages for all samples. An intense central doublet, due to (super)paramagnetic Fe 3+ is observed. The incipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…1). Comparable hyperfine structures to this 80 Kspectrum were earlier reportedly found from fitting 6 K-Mössbauer spectra for ammonium oxalate-treated samples of magnetic silt and clay fractions, of the same Collipulli soil [7,13]. From those spectra, for which all superparamagnetic relaxation effects were virtually blocked, it is plausible, by similarity, to assign the main contributions to the magnetic hyperfine structure of pattern in Fig.…”
Section: Relative Transmissionsupporting
confidence: 77%
See 1 more Smart Citation
“…1). Comparable hyperfine structures to this 80 Kspectrum were earlier reportedly found from fitting 6 K-Mössbauer spectra for ammonium oxalate-treated samples of magnetic silt and clay fractions, of the same Collipulli soil [7,13]. From those spectra, for which all superparamagnetic relaxation effects were virtually blocked, it is plausible, by similarity, to assign the main contributions to the magnetic hyperfine structure of pattern in Fig.…”
Section: Relative Transmissionsupporting
confidence: 77%
“…The B horizon presents a high clay content [13]; its φ < 53 μm portion encompasses the silt and clay fractions, according to the Soil Survey Staff of the US Department of Agriculture [15], and represent about 90% of the soil mass. Data of the chemical composition in aluminum, iron and silicon for the whole soil and for its φ < 53 μm fraction treated with three or five times with 5 mol L −1 NaOH are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…This feature was also confirmed by the relatively strong attraction of the soil mass to a hand magnet. It also has relatively high clay content (52 mass%) 20 ; the mineralogy of which is dominated by halloysite and kaolinite aluminosilicates 15,21 . At room temperature Mössbauer spectra (Figure 1) for the clay fraction of the Collipulli soil (Ultisol) are rather complex, as is usually found for most soil clay materials, and generally consist of an intense central doublet, typically due to superparamagnetic iron (oxyhydr)oxides in very small particles and/or paramagnetic species such as structural iron in the phyllosilicates, along with a variable but usually incipient sextet contribution from magnetically ordered iron (oxyhydr)oxides.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Pizarro et al 20 used OX treatments to specifically improve the Mössbauer spectra mineralogical analysis of volcanic materials. Those results, along with powder X-ray diffraction (XRD) data 21 for the clay fractions, indicated that Andisols are characterized by high contents of poorly organized aluminosilicates and iron oxides.…”
Section: Introductionmentioning
confidence: 99%
“…The higher value in the overall rate constant, k 2, of MSM on andisols with respect to DI in the same soil indicates that this value reflects contributions from the favoured electrostatic interactions considering both a retarded IPD as well as intra-OM diffusion. The way minerals present on VADS are interrelated or chemically spatially distributed, either being freely distributed throughout the soil mass or coating silt and clay grains, is determinant of their chemical role in the whole ion sorption-desorption mechanisms [28]. In this sense, the OM content is the principal component to control the pesticide sorption on andisols, as much by instantaneous equilibrium as by IPD, the presence of kaolinite, halloysite and Al/Fe oxides in Ultisols will be significant in the IPD mechanism.…”
Section: Figure 1 (A) Ipd Plots For Msm Kinetic Sorption On Ultisol mentioning
confidence: 99%